(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Urinary ascites in a newborn infant is unusual and most commonly indicates a disruption to the integrity of urinary tract, the most common cause being posterior urethral valve. We report a case of fetal urinary bladder rupture due to posterior urethral valve. The case was diagnosed antenatally by ultrasonography and after birth the diagnosis is confirmed by ascitic fluid study and imaging technique and managed successfully by participation of gynecologist, neonatologist, radiologist and urologist. Urinary ascites should be considered in a male neonate with ascites. J Bangladesh Coll Phys Surg 2024; 42: 204-208